The Activity of Combination of Hydrolyzed Virgin Coconut Oil and Chitosan Toward Wound Healing Parameters on NIH 3T3 Cells Using in Vitro Methods - Sipayung, Hekdin Marsius; Silalahi, Jansen; y, Yuandani (Asian Journal of Pharmaceutical Research and Development, 2019)
Objectives: The objective of this study was to investigate the activity of combination of hydrolyzed VCO (HVCO) and chitosan on NIH 3T3 cell proliferation activity, NIH 3T3 cell migration, COX-2 and VEGF protein expression. Design: In vitro cytotoxic assay was determined by MTT (MicrocultureTetrazoliumTehnique) assay, cell proliferation activity was measured by calculating cell viability incubated 24 hours, 48 hours and 72 hours, wound closure percentage was tested by scratch wound healing method, expression of COX-2 protein and VEGF protein were measured by immunocytochemical method. Interventions: The variable that was intervened in this study was the concentration of HVCO and chitosan. Main Outcome Measures: The main measurements carried out in this study were the absorbance value of HVCO and chitosan which was converted into viability cell, proliferation activity, percentage of wound closure, and percentage of COX-2 and VEGF protein expression. Results: Cytotoxic activity of HVCO and chitosan resulted the best concentration at 31.25 μg/ml, scratch wound healing assay from a combination HVCO and chitosan resulted the best migration of fibroblast cells at a ratio of 1:1 with HVCO 62.5 μg/ml and chitosan 62.5 μg/ml, combination of HVCO 62.5 μg/ml and chitosan 62.5 μg/ml (1:1) increased expression of COX-2 and VEGF. Conclusion: Combination of HVCO and chitosan could increase NIH 3T3 cell migration, COX-2 and VEGF protein expression. Combination of HVCO and chitosan had better wound healing activity in vitro than single use. Keywords: Rhizomucor miehei, viability, proliferation, migration, expression